Interplay between Cholesterol, SREBPs, MicroRNA-33 in Dyslipidemia - Kandhro, Abdul Hafeez (International Journal of Endorsing Health Science Research, 2016)
Dyslipidemia is characterized by elevation of plasma cholesterol, triglycerides (TGs) or both, or a low high-density lipoprotein-cholesterol (HDL-C) level that contributes to the development of insulin resistance, Diabetes mellitus type 2 (DM2) and atherosclerosis. Dietary fat and cholesterol, genetics and other risk factors are responsible for producing variations in the lipids. The cholesterol plays a major function in the body, cholesterol homeostasis mechanism is regulated by the sterol regulatory-element binding proteins (SREBPs) and firstly introduced by Brown and Goldstein. The SREBP transcription factors act coordinately with their intronic microRNAs (miRNA-33a / miRNA-33b) to regulate both fatty acid and cholesterol homeostasis. Recently, multiple studies described microRNA-33a and SREBP2 cooperation for cholesterogenic transcription to improve intracellular cholesterol levels; suggesting that therapeutic approach of miR-33 targeting antisense would imperative for reverse cholesterol transport from atherogenic macrophages, as a result reduce atherosclerosis.